Local and systemic immune responses induced by intranasal immunization with biomineralized foot-and-mouth disease virus-like particles - Li, Shuo; Zhao, Ruichong; Song, Hetao; Pan, Songjia; Zhang, Yun; Dong, Hu; Bai, Manyuan; Sun, Shiqi; Guo, Huichen; Yin, Shuanghui (Frontiers in Microbiology, 2023)
Foot-and-mouth disease virus (FMDV) infects the host by invading mucosal epithelial cells of the respiratory or digestive tract. Therefore, establishing a specific antiviral mucosal immune barrier can effectively block viral invasion. We evaluated local mucosal and systemic immune responses elicited by intranasal immunization of mice with foot-and-mouth disease (FMD) calcium phosphate mineralized virus-like particles (CaP-VLPs) and tested whether three commercial mucosal adjuvants enhanced the immunogenicity of the antigen. The biosafety of the vaccine was verified through gross observation and pathological analysis of the lungs. CaP-VLPs effectively induced secretion of IgA (sIgA) from multiple sites in mouse mucosa and produced anti-FMD-specific IgG in the serum. Splenic lymphocytes specifically proliferated and secreted IFN-γ following antigen stimulation, indicating the vaccine can induce a certain level of cellular immune response. Finally, the pathological examination confirmed that CaP-VLPs did not cause substantial damage to the lungs of animals after immunization via mucosal administration. Notably, the vaccine mixed with S adjuvant increased the content of sIgA and serum IgG, and the high level of IgG in serum was maintained at least 7 weeks. Overall, this study reveals that FMD CaP-VLPs can induce good local mucosal immune and systemic immune response through intranasal immunization, and the immune response was specifically enhanced by S adjuvant. These data support that CaP-VLPs-S as a candidate mucosal vaccine for the prevention of FMD vaccine infection.